Experiences of food abstinence in patients with type 2 diabetes: a qualitative study. Issue 1 (6th January 2016) - Buchmann, Maike; Wermeling, Matthias; Lucius-Hoene, Gabriele; Himmel, Wolfgang
Abstract : Objective: People with type 2 diabetes often report pressure to abstain from many of life's pleasures. We tried to reconstruct these patients' sense of pressure to better understand how people with diabetes make sense of, and integrate, these feelings into their life. Design, setting and participants: A secondary analysis of narrative interviews with 14 patients with type 2 diabetes who are part of a website project. Main outcome measures: Grounded theory-based analysis of narrative interviews, consisting of open, axial and selective coding. Results: People with type 2 diabetes felt obliged to give up many pleasures and live a life of abstinence. They perceived a pressure to display a modest culinary lifestyle via improved laboratory test results and weight. Their verbal efforts to reassure and distance themselves from excessiveness indicate a high moral pressure. With regard to the question of how to abstain, food and behaviour were classified into healthy and unhealthy. Personal rules sometimes led to surprising experiences of freedom. Conclusions: People with diabetes have internalised that their behaviour is a barrier to successful treatment. They experience an intensive pressure to show abstinence and feel misjudged when their efforts have no visible effect. Taking into account this moral pressure, and listening to patients' personal efforts and strategies to establish healthy behaviours, might help to build a trusting relationship with healthcare providers.